Does Stop and Search Deter Crime? Evidence From Ten Years of London-wide Data. (27th January 2018) - Tiratelli, Matteo; Quinton, Paul; Bradford, Ben
Abstract: In this article, we used ten years of police, crime and other data from London to investigate the potential effect of stop and search on crime. Using lagged regression models and a natural experiment, we show that the effect of stop and crime is likely to be marginal, at best. While there is some association between stop and search and crime (particularly drug crime), claims that this is an effective way to control and deter offending seem misplaced. We close the discussion by suggesting that, first, in a legal sense the key issue is that each and every stop should be justified in itself, not in that it has some putative wider effect on crime, and, second, in a sociological sense, our findings support the idea that stop and search is a tool of social control widely defined, not crime-fighting, narrowly defined.